2019
DOI: 10.3329/bjas.v48i1.44559
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and nutritional evaluation of wastelage using poultry droppings and napier grass

Abstract: An experiment was conducted with Napier grass (NG) treated with Poultry droppings (PD) and rice straw and ensiled with molasses to increase the nutritional and preservation quality of Napier grass. Chopped Napier grass was preserved in plastic containers under airtight condition at room temperature based on the treatments T0 (0% PD), T1 (15% PD), T2 (30% PD) and T3 (45% PD) with 5% molasses and 20% rice straw as fresh basis in each treatment to investigate physical quality, chemical composition, in vitro organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…(Harmon et al, 1975;Khatun et al, 2013). Panna et al (2019) found that 30% and 45% poultry dropings are acceptable for preparing wastelage. So, ensiling maize stover with poultry excreta and molasses will increase crude protein and other nutritive value of the diet lowering the pH value and produce lactic acid producing bacteria which will facilitate the natural preservation.…”
Section: Introductionmentioning
confidence: 99%
“…(Harmon et al, 1975;Khatun et al, 2013). Panna et al (2019) found that 30% and 45% poultry dropings are acceptable for preparing wastelage. So, ensiling maize stover with poultry excreta and molasses will increase crude protein and other nutritive value of the diet lowering the pH value and produce lactic acid producing bacteria which will facilitate the natural preservation.…”
Section: Introductionmentioning
confidence: 99%